Conflict of interest: justifying international cooperation in populist discourse - Angelos Chryssogelos; Gustav Meibauer (Frontiers in Political Science)
Contrary to the stereotypical assumption that the foreign policy of populists is geared toward conflict, much of the literature in recent years has converged on the understanding that populism results in a complex and often seemingly incoherent mix of cooperation and confrontation. Populist leaders often adopt a confrontational stance toward other states and international institutions, yet they are also capable of striking deals, defusing tensions and reconciling with multilateral settings. This inconsistency is due to a variety of factors like geopolitical and economic pressures or the thick-ideological proclivities of populists. But in this article, we are interested in how populists reconcile the contradictory trend to antagonize internationally but end up striking deals. Drawing on the literature on populist discourses and a view of foreign policy as political management of state-society relations, we argue that this reconciliation takes place primarily at a discursive level, as populists deploy a discourse of cooperation that remains consistent with the binary and Manichean logic of populism. We identify three populist discursive strategies of justifying cooperation after conflict: elite-splitting, issue-bundling and audience-hopping. We demonstrate our argument by comparing two cases of populist compromising with the EU following a protracted period of confrontation: Greece’s acceptance of a third bailout from the Eurozone under Alexis Tsipras in 2015; and Britain’s signing of a final Brexit deal under Boris Johnson in 2020.